Role of 18F-FDG PET/CT in Restrictive Allograft Syndrome After Lung Transplantation. Issue 4 (April 2019) - Verleden, Stijn E.; Gheysens, Olivier; Goffin, Karolien E; Vanaudenaerde, Bart M.; Verbeken, Erik K.; Weynand, Birgit; Van Raemdonck, Dirk E.; Verleden, Geert M.; Vos, Robin
Abstract : Background: Differential diagnosis of phenotypes of chronic lung allograft dysfunction (CLAD) remains troublesome. We hypothesized that 18 F-fluorodeoxyglucose positron emission tomography with computed tomography ( 18 F-FDG PET/CT) may help in differential diagnosis of CLAD phenotypes, as it showed promising results regarding diagnosis and prognosis in interstitial lung diseases. Methods: A monocentric, retrospective study was performed including all lung transplant recipients suffering from bronchiolitis obliterans syndrome (BOS) or restrictive allograft syndrome (RAS) who underwent 18 F-FDG PET/CT scan, in comparison with stable lung transplant recipients. Maximum standardized uptake value (SUVmax ) was associated with pulmonary function and survival. Proof-of-concept microCT and glucose transporter-1 staining served as morphologic validation for regions with different SUVmax . Results: Maximum standardized uptake value was higher in RAS (median, 2.6; n = 29) compared with BOS (median, 1.0; n = 15) and stable patients (median, 0.59; n = 8) ( P < 0.0001). In RAS, high SUVmax was associated with worse survival after 18 F-FDG PET/CT ( P = 0.0004; hazard ratio, 1.82). Forced vital capacity at 18 F-FDG PET/CT inversely correlated with SUVmax ( R = −0.40, P = 0.03). MicroCT analysis revealed extensive fibrosis in regions of high SUVmax, with an increased number of glucose transporter-1–positive cells. Conclusions: 18 F-fluorodeoxyglucose positron emission tomography with CT may noninvasively differentiate RAS from BOS. RAS patients with areas of increased lung metabolism have worse outcome, demonstrating the potential use of 18 F-FDG PET/CT during follow-up after lung transplantation.